Impact of body mass index on pulmonary complications in patients with non-Hodgkin lymphoma treated with hematopoietic stem cell transplant. Issue 11 (2nd November 2015) - Lin, Chi; Lin, Jeffmin; Stavas, Mark; Li, Sicong; Canady, Kerry J.; Romberger, Debra J.; Loberiza, Fausto R.
Abstract : The objective of this study was to examine the association between body mass index (BMI) and the incidence of pulmonary complications (PCs) after hematopoietic stem cell transplant (HCT). We reviewed 398 adult patients with non-Hodgkin lymphoma (NHL) who received autologous or allogeneic HCT between 1993 and 1997. BMI was classified as normal (18.5 < BMI ≤ 24.9), overweight (24.9 < BMI ≤ 30) and obese (BMI > 30). Multivariate logistic regression was used to analyze the relationship between BMI and presence of PCs within 100 days post-HCT while adjusting for patient-, disease- and transplant-related variables. The incidence of PCs within 100 days post-HCT was 32% ( n = 129). Median BMI was 25.4 (range: 18.6–52.2). Median age was 48.8 years (range: 19.5–73.6 years). Multivariate analysis failed to show significant association between BMI and PCs. However, a total body irradiation (TBI)-based conditioning regimen was associated with lower rate of PCs.